Histochemical study of postnatal changes in the vesicular glands of buffalo - ANURAG, ANURAG; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2014)
The postnatal changes were studied in the vesicular glands in 17 buffaloes aged 6 months, 1 to 1.5 years. 2 to 2.5 years and > 3.5 years with 5, 4, 4 and 4 animals in each group respectively. The histochemical investigations revealed that glycogen was found in the glandular cells only in 6 month-old buffalo calves. The glandular cells in older animals were positive for periodic acid Sch iff’s and alcian blue reactions. The cytoplasm of glandular epithelia and secretory material in the lumina showed stronger mercuric bromophenol blue reactions for proteins in adults. Sudanophilic lipids increased with age.